STRATEGI PENGUATAN PENGEMBANGAN KOMPETENSI PNS MELALUI KONSEP SMART TRAINING DI BPSDM KEMENTERIAN DALAM NEGERI - Hariawan Bihamding (Journal of Innovation Research and Knowledge, 2024)
The government apparatus is an essential element in this country whose functions are as a dynamist and catalyst for driving development, public services, and governance management at large. The success or failure of achieving state goals is mainly determined by the commitment, quality, and competence of its apparatus. It is necessary to realize that the development of civil servant competency has not currently achieved optimal results, there are many obstacles faced, especially funding and output problems or achievement of results that have not met expectations. These become the reason for the author to conduct research entitled "Strategy for Strengthening Civil Servant Competency Development Through the SMART Training Concept at the Human Resources Development Agency (BPSDM) - Ministry of Home Affairs". A descriptive qualitative approach was carried out by analyzing and describing feasible strategies to strengthen the development of civil servant competencies in the BPSDM. One of the strategies used is the SMART Training concept, which was formulated to create very efficient and practical training, reducing the obstacles encountered so far. Data was collected through observation, interviews, and documentation for further reporting and presentation in this research. This study was conducted from October 2023 to February 2024. Informants from BPSDM in particular and from the Ministry of Home Affairs in general participated. The result obtained showed the pattern of competency development implemented at the BPSDM has yet to carry out too many significant innovations and changes toward an ideal level. This argument underlined the urgency of implementing the SMART Training concept in the BPSDM. Based on 518 informants, the SMART Training concept is a hope and a breakthrough in creating an effective and efficient competency development model, prioritizing independent learning, emphasizing technology transformation, and increasing authentic civil servant competency